Global Schauder decompositions of locally convex spaces - Venkova, Milena (Mathematica Scandinavica, 2007)
We define global Schauder decompositions of locally convex spaces and prove a necessary and sufficient condition for two spaces with global Schauder decompositions to be isomorphic. These results are applied to spaces of entire functions on a locally convex space.